The couch grass rhizome with Heterobasidion annosum fruiting bodies in afforested post‐agricultural land. Issue 4 (21st June 2016) - Sierota, Z.; Damszel, M.; Borys, M.; Nowakowska, J. A.
Summary: The pathogenic fungus Heterobasidion annosum was identified in the rhizome of a couch grass ( Elymus repens) using genetic markers. The couch grass grew in the proximity of a Scots pine stand that was visibly affected by the pathogen. The rDNA analysis showed 100% sequence similarity between two H . annosum sequences of ITS1 and ITS2 obtained from fruiting bodies found on the couch grass rhizome and on the stem of the Scots pine. These results indicate a close relationship between the two isolates of H. annosum and that they are derived from a common ancestor. The results show that H. annosum mycelia can infect couch grass rhizomes and subsequently produce fruiting bodies. It also suggests that the known modes of infection of tree roots by this pathogen in coniferous stands should take into account couch grass rhizomes in the dispersal of the disease in afforested post‐agricultural soils.